Guevara's legacy - Abd Razak, Dzulkifli (2003)
TO understand current advances in biomedical sciences in Cuba, it is useful to trace back the thoughts of some of the early architects of the nation. One of them was Ernesto Che Guevara (19281967). Thirtysix years ago more specifically, at 1.10pm on Oct 9, Guevara was murdered in Bolivia. It was one of the saddest moments in Cuban history. His remains were only discovered six years ago, in Vallegrande, Bolivia, and repatriated to Cuba. That Guevera was also a qualified medical doctor made it even more poignant. Indeed it was his medical training that turned him into a committed revolutionary. Perhaps his speech entitled On Revolutionary Medicine, delivered in I960, a year after the downfall of the former regime, will help us to understand what changes the man and his profound thoughts brought to the future of medicine and medical research in Cuba.